CORRELATION BETWEEN KNOWLEDGE AND ATTITUDE OF RURAL DWELLERS ON COMMUNITY BASED- FOREST MANAGEMENT IN COMMUNITIES AROUND SHASHA FOREST RESERVES AREA OF OSUN STATE, NIGERIA - Aluko, Olawale Julius; abolade, Adekunle; Oluwatobi Paul, Olusina (FUDMA Journal of Sciences, 2025)
This study assessed the correlation between the knowledge and attitudes of rural dwellers regarding community-based forest management (CBFM) in communities surrounding the Shasha Forest Reserve in Osun State, Nigeria. A multistage sampling technique was employed, with 103 household heads interviewed through structured questionnaires and personal interviews. The findings indicated that a significant majority (60.2%) of respondents possessed a high level of knowledge about CBFM initiatives, which was positively correlated with their attitudes. Specifically, 57.3% of respondents demonstrated a favorable attitude towards these initiatives, suggesting that increased knowledge enhances positive perceptions of community forest management practices. Furthermore, the analysis revealed a significant relationship between knowledge and attitudes (R-value = 0.593, P-value = 0.050), indicating that improved knowledge among community members could lead to more effective participation in sustainable land use practices. The results underscore the importance of empowering local communities through education and involvement in decision-making processes to promote sustainable forest management and address environmental challenges in the region. This study contributes valuable insights into the dynamics of community engagement in forest management and the potential for enhancing environmental sustainability through informed local participation.
Keywords: Forest Management; Knowledge; Attitude; Forest Reserves; Initiatives